Opportunities for CRISPR/Cas9 Gene Editing in Retinal Regeneration Research - Campbell, Leah J.; Hyde, David R. (Frontiers in Cell and Developmental Biology, 2017)
While retinal degeneration and disease results in permanent damage and vision loss in humans, the severely damaged zebrafish retina has a high capacity to regenerate lost neurons and restore visual behaviors. Advancements in understanding the molecular and cellular basis of this regeneration response give hope that strategies and therapeutics may be developed to restore sight to blind and visually-impaired individuals. Our current understanding has been facilitated by the amenability of zebrafish to molecular tools, imaging techniques, and forward and reverse genetic approaches. Accordingly, the zebrafish research community has developed a diverse array of research tools for use in developing and adult animals, including toolkits for facilitating the generation of transgenic animals, systems for inducible, cell-specific transgene expression, and the creation of knockout alleles for nearly every protein coding gene. As CRISPR/Cas9 genome editing has begun to revolutionize molecular biology research, the zebrafish community has responded in stride by developing CRISPR/Cas9 techniques for the zebrafish as well as incorporating CRISPR/Cas9 into available toolsets. The application of CRISPR/Cas9 to retinal regeneration research will undoubtedly bring us closer to understanding the mechanisms underlying retinal repair and vision restoration in the zebrafish, as well as developing therapeutic approaches that will restore vision to blind and visually impaired individuals. This review focuses on how CRISPR/Cas9 has been integrated into zebrafish research toolsets and how this new tool will revolutionize the field of retinal regeneration research.